“OSOB WALIKAN”: ENVISIONING HOW MALANGESE MAINTAIN THEIR EXISTENCE - Fadhillah, Syahnidar Ravena; Sudarwati, Emy (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2023)
Osob Walikan, commonly referred to as Walikan Malang, can be widely used in the social life of Malang people. Developed from a code language, this language still exists even though it already served its purpose and developed into a Malang local language. This paper investigates the current perception of Malangese toward Walikan and its relationship with the maintenance of the Walikan language, which is a local code street language that has shifted to become an urban language. This qualitative study uses questionnaires and interviews to gather the data. The findings showed that there are 3 main perceptions of Malangese towards Walikan: a language as an identity, cultural heritage, and symbol of solidarity. The majority of participants agreed that Walikan is important and needs to be preserved because Walikan has its values for the Malang people. The main method of preservation is to use this language actively in communication so that there are always active speakers to prevent the decline of language use.